Investigating the impact of microbiome-changing interventions on food decision-making: MIFOOD study protocol - Meghedi Vartanian; Konrad Jakob Endres; Yee Teng Lee; Silke Friedrich; Marie-Theres Meemken; Imke Schamarek; Kerstin Rohde-Zimmermann; Robin Schürfeld; Lina Eisenberg; Anja Hilbert; Frauke Beyer; Michael Stumvoll; et al. (BMC Nutrition)
Abstract Background Obesity is a multifactorial disease reaching pandemic proportions with increasing healthcare costs, advocating the development of better prevention and treatment strategies. Previous research indicates that the gut microbiome plays an important role in metabolic, hormonal, and neuronal cross-talk underlying eating behavior. We therefore aim to examine the effects of prebiotic and neurocognitive behavioral interventions on food decision-making and to assay the underlying mechanisms in a Randomized Controlled Trial (RCT). Method This study uses a parallel arm RCT design with a 26-week intervention period. We plan to enroll 90 participants (male/diverse/female) living with overweight or obesity, defined as either a Waist-to-Hip Ratio (WHR) ≥ 0.9 (male)/0.85 (diverse, female) or a Body Mass Index (BMI) ≥ 25 kg/m2. Key inclusion criteria are 18–60 years of age and exclusion criteria are type 2 diabetes, psychiatric disease, and Magnetic Resonance Imaging (MRI) contraindications. The interventions comprise either a daily supplementary intake of 30 g soluble fiber (inulin), or weekly neurocognitive behavioral group sessions, compared to placebo (equicaloric maltodextrin). At baseline and follow-up, food decision-making is assessed utilizing task-based MRI. Secondary outcome measures include structural MRI, eating habits, lifestyle factors, personality traits, and mood. Further, we obtain fecal and blood samples to investigate gut microbiome composition and related metabolites. Discussion This study relies on expanding research suggesting that dietary prebiotics could improve gut microbiome composition, leading to beneficial effects on gut-brain signaling and higher-order cognitive functions. In parallel, neurocognitive behavioral interventions have been proposed to improve unhealthy eating habits and metabolic status. However, causal evidence on how these “bottom-up” and “top-down” processes affect food decision-making and neuronal correlates in humans is still scarce. In addition, microbiome, and gut-brain-axis-related mediating mechanisms remain unclear. The present study proposes a comprehensive approach to assess the effects of these gut-brain-related processes influencing food decision-making in overweight and obesity. Trial registration ClinicalTrials.gov NCT05353504. Retrospectively registered on 29 April 2022.